Organotin contamination, imposex and androgen/oestrogen ratios in natural populations of Nassarius reticulatus along a ship density gradient - Barroso, C. M. (2005)
Levels of organotin body burden (expressed as tin), imposex and steroid hormones (testosterone, 17β-oestradiol, testosterone glucuronide and sulfate conjugates) were investigated in natural populations of Nassarius reticulatus in the Ria de Aveiro (northwest Portugal) between 1997 and 1999. The tributyltin (TBT) whole body burden (b.b.) of females presented increasing gradients from the adjacent open coast (16–26 ng g−1 dry weight (d.w.)) towards the ports inside the Ria de Aveiro (195–272 ng g−1 d.w.). Triphenyltin b.b. was only detected at the most polluted port (22 ng g−1 d.w.). Imposex also presented increasing values from the adjacent coast (vas deferens sequence index (VDSI): 0.0–0.5; relative penis length index (RPLI): 0.0–2.4; penis length index (PLI): 0.0–0.3 mm; percentage of affected females (%I): 0–30) towards the ports (VDSI: 3.8–4.8; RPLI: 51–80; PLI: 6.7–10.8 mm; %I: 100). The testosterone levels in females without imposex were always lower than in females with imposex, and the ratio of testosterone/17β-oestradiol in females tended to increase with increasing imposex and organotin contamination. In spite of the large difference in the female testosterone and 17β-oestradiol levels between summer and winter, related to the reproductive cycle, the spatial trend of the testosterone/17β-oestradiol ratio was remarkably similar in shape and values in the two seasons. Imposex was significantly correlated with the TBT b.b. and the testosterone/17β-oestradiol ratio in females. The testosterone conjugate levels did not show any clear pattern with the increasing values of imposex and TBT contamination. Copyright © 2005 John Wiley & Sons, Ltd.